(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
The article deals with the process of changing the vector of state policy in the field of foreign language learning in the 20-50s of the XX century. After the October Revolution, they stopped the study of a foreign language because they regarded it as a relic of the past, an antagonistic society with a pronounced and irreconcilable class nequality. However, in 1923, Nadezhda Konstantinovna Krupskaya denied the need to study Esperanto on a national scale in her article " Teaching Foreign Languages " and described the practical significance, main goal and priority method of teaching a foreign language and more than that her own position about the role of foreign languages, thereby laying the foundation for its study for many decades. The article analyzes teaching foreign languages culturological idea, as it was represented by V.I. Lenin, N.K. Krupskaya, I.V. Stalin, as well as some public and scientific figures. We pay particular attention to the founder of " new language doctrine " Academician N.Ya. Marra’s linguistic ideas. Their reflections and statements about foreign languages educational and cultural potential, their definition of the purpose of their study not only laid the foundation for domestic language education in the young Soviet state, but also determined the vector of studying foreign languages in the future.